Do trained nurses feel more psychologically safe?-Results from a multi‐level modelling approach - Melissa Seibert; Holger Pfaff; Nadine Scholten; Ludwig Kuntz (Wiley, 2021)
Abstract Aim To analyse the associations between a nurse's psychological safety and her/his additional training. Design A cross‐sectional survey conducted between September 2015 and August 2016. Methods A multi‐level modelling approach was used considering unit membership. We used data from 1,239 questionnaires completed by nurses on 75 different German neonatal intensive care units, and 75 questionnaires completed by the corresponding leading nurse. Results We found the additional managerial training as a charge nurse to be a positive predictor for psychological safety (β = .346, p ≤ .05). Surprisingly, the additional clinical training in paediatric intensive care is negatively associated with psychological safety (β = −.192, p ≤ .01). Our model estimates that this negative association can be inhibited if the team's share of nurses with an additional clinical training increases (β = .313, p ≤ .05).